2018
DOI: 10.1007/s13205-018-1091-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure and catalytic mechanism of fungal family G acidophilic xylanases

Abstract: Industrial applications of xylanases have made this enzyme an important subject of applied research work. Function of this particular enzyme is to degrade or hydrolyze the plentiful polysaccharide xylan, an important component of hemicellulose. It mainly cleaves the backbone of xylan that is made up of a number of xylose residues connected with β-1,4-glycosidic linkages. Fungi with mycelia are regarded as the best producer of xylanases. These varied xylanases not only differ in their sizes and shapes but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…In our study, the results suggest that enzyme production was maximal at an acidic pH of 5. Researchers have found that breakdown of xylan in LC biomass is accelerated by acidic media which makes the substrate more sensitive and ultimately enzymes can work more efficiently [ 46 ]. Literature suggests that acidic xylanases have many potential industrial applications including in bio-bleaching, fruit juice clarification, or xylooligosachharides production [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the results suggest that enzyme production was maximal at an acidic pH of 5. Researchers have found that breakdown of xylan in LC biomass is accelerated by acidic media which makes the substrate more sensitive and ultimately enzymes can work more efficiently [ 46 ]. Literature suggests that acidic xylanases have many potential industrial applications including in bio-bleaching, fruit juice clarification, or xylooligosachharides production [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analogous behavior was observed by Few research addresses mutagenesis directed at changing the optimal pH of enzymes. In general, the proposed strategies focus on modifying the surface charges of the molecule (Yang et al, 1993), changing the values of the acid dissociation constants of the catalytic residues (Dey et al, 2018;Li et al, 2019), and cavity lling (Nielsen et al, 2000). In particular, Shi et al (2022) replaced amino acids near catalytic residues to modify the optimal pH of the β-galactosidase from Aspergillus oryzae.…”
Section: Place Fig 3 Herementioning
confidence: 99%
“…YM55-1 and shifted its pH optimum from 9.0 to 8.0. Commonly, the pKa values of the catalytic residues decide the pH profile of enzymes (Dey and Roy, 2018). Since the ionization states of catalytic residues are vital in terms of the enzymatic catalyzation of a specific reaction, mutation design is usually based on comparative enzyme engineering.…”
Section: Introductionmentioning
confidence: 99%